Pengaruh Konseling Kelompok dengan Teknik Self-management Terhadap Perilaku Agresif Siswa - Anastashya Anggraini; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Journal of Education and Counseling (JECO), 2022)
The research was motivated by the of aggressive behavior of grade VIII MTS students Muttallimin Pandegalang Year 2020/2021. The purpose of the study was to find out a picture of students' aggressive behavior and the influence of group counseling with technique Self-management in reducing aggressive behavior. This type of research is a pre-experimental design with one group pre- post-test design, with a class VIII population of 54 students with a sample of 8 students selected using purposive sampling techniques. Data collection method using questionnaires of aggressive behavior of students who have tested the validity of the content and have 44 items out of 60 valid items, the study result found 8 students in the very high category with a percentage of 15%. 20 students in the high category with a percentage of 37%, and 24 students in the moderate category with a percentage of 44%, and 2 students in the low category with a percentage of 4%. Data analysis techniques using wilxocon tests. Results of analysis of pre-test data and post-test aggressive behavior. obtained z count – 2,521 <z table 36.00, then Ha accepted and Ho rejected, meaning it can reduce aggressive behavior after being given group counseling services with Self-management techniques to students of grade VIII MTS Muttallimin Pandeglang.